PENGARUH JUMLAH PENDUDUK DAN PDRB TERHADAP KEMISKINAN: ZAKAT SEBAGAI MODERASI - Amran, Ellyana; Parinduri, Aina Zahra (Media Ekonomi, 2023)
Analyzing the impact of population and GRDP on poverty in DKI Jakarta with Zakat as a moderating variable. The research method is a quantitative method with a saturated sample, that is, all members of the population are used as samples. The data source is secondary data with a panel model. The data analysis technique used is multiple regression with moderation variables and using the SPSS application. There is an effect of population on poverty rate; there is an effect of GRDP on poverty rate; zakat cannot moderate the effect of population on poverty rate; zakat cannot moderate the effect of GRDP on poverty rate.